PEMBERDAYAAN DAN TANTANGAN MONETESASI BERBASIS POTENSI LOKAL DESA WISATA KARANGASEM BANTUL (Forum Ilmu Sosial, 2016)
This article discusses the experience UGM Tourism Diploma Course in assisting the people of Karangasem Hamlet, Village Muntuk, Dlingo subdistrict, Bantul, the pioneer of rural tourism since 2014. The vast majority (95%) Karangasem Dusun community for decades is hereditary has become a bamboo craftsman, with a product that initially only the tray and place the rice and then developed into a variety of furniture and other household needs. Seeing the local potential, Tourism Diploma Program UGM thought to encourage communities to develop tourism in the village. Moreover, in addition to the potential of culture held, this village also has the potential of nature tourism in the form of a view of the landscape, streams and pine forests. The smooth passage of the two-year community development activities is due to the character of the people who want to move forward and not money oriented. But over time, the tourism activities that are profit-oriented will inevitably push changes the character of the community. This paper would like to see further how community strategies to deal with monetesasi Karangasem and map out strategies UGM further prepared to continue to assist the people of Karangasem with characters that might change in building a tourist village in the hamlet. The method used to collect data in this descriptive study is participatory and interviews while this article is presented with descriptive analytical.